Transatlantic Trade and Investment Partnership – Is it a Lever to Create Free Trade? (Economic and Political Thought, 2014)
The Transatlantic Trade and Investment Partnership is a proposal that cancompletely change the contemporary structure of global trade relations. Dueto the role and importance of the economic exchange between the partiesto the future free trade agreement: the European Union and the UnitedStates, the rules of liberalisation negotiated by them can change the present,universal order within the WTO system. Having taken into considerationthe increasing number of agreements that create new free trade areas, onecan say that the thesis that, as a result of that phenomenon, there is anincreasing fragmentation of global trade seems to be confirmed in practice.What the benefits are going to be will depend on the balance of trade changesand development. At the same time, what the costs are going to be forparticular parties to the global economic exchange will mainly depend ontheir national economies’ ability to meet challenges adequately. It is wellknown that developed countries and their multinational companies cope withsuch conditions best. New rules of global economic exchange are createdand the positive effects of these changes in that exchange concentrate in thisarea. Although there are attempts to make developing countries beneficiariesof the world trade liberalisation, e.g. the Bali Package within the WTO, thepositive effect of these initiatives is more hypothetical than real for them.